Levosimendan in venoarterial ECMO weaning. Rational and design of a randomized double blind multicentre trial - Omar Ellouze; Agnès Soudry Faure; Mohamed Radhouani; Osama Abou‐Arab; Emmanuel Besnier; Mouhamed Moussa; Amélie Cransac; Elea Ksiazek; Marc‐Olivier Fischer; Paul Michel Mertes; Belaid Bouhemad; Pierre Grégoire Guinot (ESC Heart Failure, 2021)
Abstract Aims Venoarterial extracorporeal membrane oxygenation (VA‐ECMO) is increasingly being used in circulatory failure. The main indications are cardiogenic shock, post‐cardiotomy cardiac failure, and refractory cardiac arrest. However, VA‐ECMO weaning is particularly challenging, and weaning failure is reported to be as high as 50%, with increased related mortality. Levosimendan is a novel long acting effect inodilator used in cardiogenic shock and terminal heart failure decompensation. Levosimendan use in VA‐ECMO patients seems to reduce weaning failure regardless of the initial aetiology and to reduce mortality when administrated early after VA‐ECMO initiation. However, studies are limited to retrospective analyses and reported case series. The aim of the WEANILEVO trial is to evaluate whether administration of levosimendan before VA‐ECMO weaning is associated with a reduced rates of weaning failure and recourse to other temporary circulatory support. Methods and results WEANILEVO is a randomized, prospective, multicentre, double‐blind, parallel‐group, controlled trial. One hundred eighty patients will be enrolled if they had acute circulatory heart failure treated with VA‐ECMO and for whom weaning is expected within 48 h. The study drugs are either levosimendan (0.2 μg/kg/min for 24 h) or a placebo. The primary endpoint of the trial is the absence of VA‐ECMO weaning, recourse to another VA‐ECMO, or other temporary circulatory assistance or death within 7 days of VA‐ECMO weaning. Conclusions Levosimendan use in VA‐ECMO appears to be beneficial for reducing weaning failure and mortality. The results of WEANILEVO should significantly influence decisions regarding the use of levosimendan for VA‐ECMO weaning.